Use and misuse of statins after ACS: analysis of a prescription database of a community setting of 2,042,968 subjects - Maggioni, Aldo P; Rossi, Elisa; Cinconze, Elisa; De Rosa, Marisa (European journal of preventive cardiology, 2014)
To assess in a community setting how patients discharged alive after an acute coronary syndrome (ACS) are treated with statins. Specifically, the rate of prescription, the dosages, and 1-year adherence have been evaluated. From the ARNO Observatory, we carried out a record linkage analysis of discharge records for ACS and prescription databases, which included 2,042,968 subjects of seven local health authorities from northern to southern Italy. The accrual period lasted from 1 January to 30 June 2007. Logistic regression analysis was performed to identify the independent predictors of prescription continuity. Of the 2,042,968 subjects, 1.5‰ were hospitalised for ACS over the 6 months, 58% of patients were aged more than 70 years, and females accounted for 33% of the cases. In-hospital all-cause death was 7.4%. Of the patients discharged alive, 80.7% received a statin treatment. High dosage of statins were used only in a minority of cases. After 1-year follow up, adherence to treatment was observed in 67.2% of patients. Older age and the presence of comorbidities were independently associated with a better prescription continuity, while presence of cancer or depression was associated with a poor prescription continuity. In a community setting, the rate of prescription of statins seems to be satisfactory. However, the dosages of statins suggest that the recommendation to use intensive statin treatment seems to be not adequately followed. Further, prescription continuity over time was suboptimal. There is still a relevant gap between evidence-based recommendations and what actually happens in routine clinical practice.